Fail to prepare and you can prepare to fail: the experience of financing path changes in teaching hospitals in Iran. Issue 1 (December 2016) - Doshmangir, Leila; Rashidian, Arash; Jafari, Mehdi; Ravaghi, Hamid; Takian, Amirhossein
Abstract Background In 1995, teaching and public hospitals that are affiliated with the ministry of health and medical education (MOHME) in Iran were granted financial self-sufficiency to practice contract-based relations with insurance organizations. The so-called "hospital autonomy" policy involved giving authority to the insurance organizations to purchase health services. The policy aimed at improving hospitals' performance, hoping to reduce government's costs. However, the policy was never implemented as intended. This was because most participating hospitals gave up to implement autonomous financing and took other financing pathways. This paper analyses the reasons for the gap between the intended policy and its execution. The lessons learned from this analysis can inform, we envisage, the implementation of similar initiatives in other settings. Methods We conducted semi-structured interviews with 28 national and 13 regional health policy experts. We also gathered a comprehensive and purposeful set of related documents and analyzed their content. The qualitative data were analyzed by thematic inductive-deductive approach. Results We found a number of prerequisites and requirements that were not prepared prior to the implementing hospital autonomy policy and categorized them into policy content (sources of funds for the policy), implementation context (organization of insurance organizations, medical tariffs, hospitals' organization, feasibility of policy implementation, actors and stakeholders' support), and implementation approach (implementation method, blanket approach to the implementation and timing of implementation). These characteristics resulted in unsuitable platform for policy implementation and eventually led to policy failure. Conclusions Autonomy of teaching hospitals and their exclusive financing through insurance organizations did not achieve the desired goals of purchaser-provider split in Iran. Unless contextual preparations are in place, hospital autonomy will not succeed and problematic financial relations between service providers and patients in autonomous hospitals may not be ceased as a result.